Environmental geomechanics - Schrefler, B. A.; Delage, Pierre (London : ISTE, 2010)
This title covers topics that are of increasing importance in engineering practice: natural hazards, pollution and environmental protection through good practice. The first part of the book deals with natural risk factors, of both natural and human origin, that should be borne in mind. The second part is devoted to pollution and polluted sites and their repercussions, a facet of growing significance given the increasing reclamation of land from abandoned industrial sites for urban development over the last 20 years. Different types of oil pollution and methods of decontamination are described, followed by a discussion of waste management and detailed coverage of confinement liners used in surface waste disposal.
Soil collapse due to water infiltration -- The nature and survey of soil pollution -- Subsidence phenomena -- Subsidence induced by fossil fuels extraction -- Physics of water transfers in stone -- Experimental characterization techniques of alterations -- Liners for waste containment facilities -- Retention and transfer of soluble chemical pollutants : mechanisms and numerical modelling -- Case studies.
Includes bibliographical references and index.
Print version record.
Keywords: Environmental geotechnology; Soil pollution; Electronic books